2013
DOI: 10.1073/pnas.1304437110
|View full text |Cite
|
Sign up to set email alerts
|

Family-based training program improves brain function, cognition, and behavior in lower socioeconomic status preschoolers

Abstract: Using information from research on the neuroplasticity of selective attention and on the central role of successful parenting in child development, we developed and rigorously assessed a familybased training program designed to improve brain systems for selective attention in preschool children. One hundred forty-one lower socioeconomic status preschoolers enrolled in a Head Start program were randomly assigned to the training program, Head Start alone, or an active control group. Electrophysiological measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
252
6
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(280 citation statements)
references
References 59 publications
14
252
6
8
Order By: Relevance
“…They tend to experience more serious adversities at an early age that may lead to learned sustained vigilance, leading to focus attention on the identification of threats and missing relevant information as it seems to happen in intellectually demanding contexts like classrooms (Neville et al, 2013;Schibli & D'Angiulli, 2011;Shackman, Shackman, & Pollack, 2007 Consistent with these findings the work of Neville et al (2013) has shown positive outcomes among socially disadvantaged pre-kinder students. According to Neville et al (2013), several weeks after the implementation of the Family-Based Training Program with children and parents, they observed significant improvements in attention and other cognitive functions. The inclusion of parents is part of the Family-Based Training Program.…”
Section: Attention Among Low-income Studentssupporting
confidence: 65%
See 3 more Smart Citations
“…They tend to experience more serious adversities at an early age that may lead to learned sustained vigilance, leading to focus attention on the identification of threats and missing relevant information as it seems to happen in intellectually demanding contexts like classrooms (Neville et al, 2013;Schibli & D'Angiulli, 2011;Shackman, Shackman, & Pollack, 2007 Consistent with these findings the work of Neville et al (2013) has shown positive outcomes among socially disadvantaged pre-kinder students. According to Neville et al (2013), several weeks after the implementation of the Family-Based Training Program with children and parents, they observed significant improvements in attention and other cognitive functions. The inclusion of parents is part of the Family-Based Training Program.…”
Section: Attention Among Low-income Studentssupporting
confidence: 65%
“…According to Neville and colleagues, parents attended two-hour classes during eight weeks plus some additional exercises that they had to perform with their children at home. At the end of the intervention program the children showed greater improvements in several aspects like neural measures of attention, language and IQ (Neville et al, 2013). Parents' participation seems to have been central to the improvements of children's attention and learning.…”
Section: Attention Among Low-income Studentsmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings highlight the importance of frequently monitoring children's academic development to identify early signs of risk and initiate appropriate interventions quickly to prevent or remediate academic delays. Data from intervention programs conducted with typically developing children suggest that some forms of training in EF are supportive and enable children to learn complex tasks efficiently and engage in the higher-order problem solving that is required for school success [9,27,28]. Research into successful interventions with children in the general population, including interventions for reading, math, To aid interpretation, the estimated beta coefficients are reported as the estimated change in academic outcome for each 10-point increase in memory or executive function predictor, after rescaling each of the predictors to a 100-point scale.…”
Section: Discussionmentioning
confidence: 99%